Answer:
Step-by-step explanation:
y intercept
To find the y intercept, make x = 0
2(0) + y = - 6 zero times anything is 0
0 + y = -6
The y intercept is (0,-6)
x intercept
The x intercept happens when y = 0
2x + 0 = -6 zero added to anything = whatever you started with.
2x = - 6 Divide by 2
2x/2 = -6/2 Do the division
x = - 3
The x intercept = (-3,0)
Formula :
Base²= Hypotenuse² - Perpendicular ²
Remember the a² in formula has nothing to do with the a we have to find. :)
You can buy 10 pounds of melons
Answer:
Step-by-step explanation:
1) divide each term in the numerator by the term in denominator:
(remember when dividing subtract the smaller exponent from larger exponent
for example: say a is the larger exponent, do
x^4/x=x^3
5x^3/x=5x^2
3x^2/x=3x
so
x^3+5x^2+3x
hope this helps!
Answer:
i dont know
Step-by-step explanation: